An evaluation of the new tourist behavior model based on the extended theory of planned behavior - Trong Tien Bao Bui (Journal of Tourism, Heritage & Services Marketing, 2022)
Purpose: The current study aims to evaluate and validate travel intention through the extended theory of planned behaviour (TPB) and overall image of the destination, e-WOM, that travel intention linked to actual tourist behavior. Methods: A sample of 389 domestic tourists was empirically exaimined, and analysed by using the partial least squares structural equation modelling (PLS-SEM) technique in order to demonstrate that the new conceptual model has a power to an insight understanding of tourist behaviour. Results: The major findings of the study identified that the influence of e-WOM on the original TPB and overall destination image constructs was statistically confirmed. In addition, destination image is as mediating variable linking between e-WOM and travel intention, which in turns lead to increasing actual tourist behavior. Implications: The major findings of the current study are useful for local authority in enhancing positive image of the destination and particularly e-WOM to increase travel intention and lead to better predicting tourist behaviour. This study further provides some theoretical and managerial implications to comprehensive understand travel intention.
Keywords: L83; B16; 330; Destination image; e-WOM; travel intention